Richard Simon Critical History of the Text of the New Testament : ""Wherein Is Established the Truth of the Acts on Which the Christian Religion Is Based"" - Hunwick, Andrew W. R. (New Testament tools, studies and documents., 2013)
In Critical History of the Text of the New Testament (1689), 17th century Oratorian Richard Simon (1638-1712), 'father' of modern biblical criticism, surveys the genuineness, authority, and reliability of all then known manuscript and printed sources of the New Testament.